Penerapan Hydrotherapy Inovatif Berbantuan Speeder Equipment untuk Meningkatkan Kualitas Hidup Lansia dengan Osteoarthritis dan Low Back Pain - Septian, Regi Dwi; Mudjihartono, Mudjihartono; Rahmat, Alit; Nugraha, Reshandi; Karim, Naufal Nur Fadhillah; Fitriani, Tika (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to provide a non-pharmacological solution to reduce joint pain and improve the quality of life of older adults with Osteoarthritis (OA) and Low Back Pain (LBP) through a hydrotherapy program using Speeder Equipment. The program involved 30 participants from the swimming community in the Greater Bandung area who participated in progressive training sessions focused on joint mobility, flexibility, and relaxation. The instruments used included the Visual Analogue Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Oswestry Disability Index (ODI), and the World Health Organization Quality of Life–Older Adults Module (WHOQOL-OLD). Data were analyzed descriptively and further examined using Pearson’s Product-Moment correlation. The results showed a 22.5% reduction in pain levels among the OA group and an 18.9% reduction among the LBP group, along with a 16.7% improvement in joint function and a 14.3% increase in quality-of-life scores. Hydrotherapy using Speeder Equipment proved to be safe, effective, and beneficial both physically and psychosocially, while also enhancing participants’ social engagement. This program is expected to serve as a sustainable community-based therapeutic model to improve the health and well-being of older adults.